Behaviors of Pipe-Soil Interaction on Unstable Slopes by Finite Element Simulation - Susila, Endra; Agrensa, Fico (Jurnal Teknik Sipil, 2018)
AbstractPipe-soil interaction plays an important role to the pipe stress analysis subjected to soil movement due to slope instability and/or slope failure.  As the soils / slopes begin to fail, a single pipe or a group of pipes buried inside failure zone will bear additional loads which frequently lead to overstress or buckling.  To study this phenomena, a case study was carried out by modelling a group of pipes subjected to ground movement in lateral direction. ABAQUS, a finite element software was employed to establish a 3 D numerical model of pipe-soil interaction during landslide event. Discussions of the results of this analysis are presented by focusing on the behaviors of displacement and stress of the pipes due to slope failure.  Based on the analysis results, the length of failure zone becomes the major cause of the location of maximum stress during slope failure, it should be assessed carefully.AbstrakPada analisis pipe-stress dengan beban dari pergerakan tanah yang diakibatkan oleh longsoran, perilaku interaksi antara pipa dan tanah berperan sangat penting. Ketika tanah/lereng mulai bergerak, sebuah pipa atau beberapa pipa yang dipasang di dalam bidang kelongsoran akan menerima beban tambahan yang seringnya menyebabkan buckling/overstress pada pipa. Untuk mempelajari fenomena ini, studi kasus dilakukan dengan memodelkan grup pipa yang dikenai pergerakan tanah secara lateral. ABAQUS, sebuah program berbasis finite element digunakan untuk memodelkan interaksi antara pipa dan tanah secara tiga dimensi selama longsor terjadi. Diskusi mengenai hasil dari analisis ini dilakukan dengan berfokus kepada perilaku displacement dan stress dari pipa akibat longsoran tanah. Berdasarkan hasil analisis, panjang dari bidang longsor menjadi issue utama dalam penentuan lokasi stress maksimum pipa, sehingga ke depannya perlu dilakukan pemeriksaan secara detail.